The Influence of GDM Liquid Organic Pupils On The Onion Growth of Palu Valley (Allium wageki Araki.) and Its Use As Learning Resources - Muhammad Arihidayat; Lestari M.P. Alibasyah; Hayyatun Mawaddah (CV. Dharma Samakta Edukhatulistiwa, 2024)
GDM liquid organic fertiliser is an organic-based fertiliser or nutrient that contains complete nutrients according to plant needs. This study aims to describe information on the effect of GDM liquid organic fertiliser on shallot plants of Palu Valley variety and determine the best dose in its use. This research is an experimental study using a completely randomised design (CRD), consisting of 5 treatments with 4 replications. The treatments consisted of P0 = Control (without fertiliser), P1 = 2 ml/polybag, P2 = 4 ml/polybag, P3 = 6 ml/polybag, P4 = 8 ml/polybag. Data analysis used ANOVA test and continued with BNT test. The results showed that the treatment of GDM liquid organic fertiliser had a significant effect on the growth of shallot plants of Palu Valley varieties, and the best dose for plant growth was P3= 6 ml/polybag. The results of this study were then utilised as a learning resource in the form of a practical guidebook. Based on the validation test and trial on students, the results of the research can be utilised declared feasible as a learning resource with an average percentage of assessment results of 89.34%.